2009
DOI: 10.1002/hyp.7309
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal patterns of nutrient concentrations and export in a north‐eastern European lowland catchment

Abstract: Abstract:In 2002-2004 we undertook six sampling campaigns during representative hydrological stages in a 901 km 2 Estonian lowland catchment to quantify the spatial and seasonal variability of in-stream dissolved inorganic nitrogen (DIN) and dissolved reactive phosphorus (DRP) concentrations and to identify the influence of land cover and landscape structure. Using a synoptic approach we mapped concentrations in all stream orders. Using linear regression, the relations between the share of agricultural land an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Stronger linkages between land use in corridor areas and in‐stream nutrient conditions, as opposed to the entire catchment, have been documented in other studies (e.g. Osborne and Wiley, ; Mourad and van der Perk, ), but not all (e.g. Omernik, ; Hunsaker and Levine, ).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Stronger linkages between land use in corridor areas and in‐stream nutrient conditions, as opposed to the entire catchment, have been documented in other studies (e.g. Osborne and Wiley, ; Mourad and van der Perk, ), but not all (e.g. Omernik, ; Hunsaker and Levine, ).…”
Section: Discussionmentioning
confidence: 61%
“…The relationship between in‐stream nutrient concentrations and land use has been demonstrated to be strongly and positively linked to stream‐flow conditions (e.g. Petry et al ., ; Buck et al ., ; Mourad and van der Perk, ; Chun et al ., ). Given that stream flow is strongly associated with precipitation conditions and associated runoff in the catchment areas, wetting or drying conditions within the catchment should result in the expansion or contraction of the areas of land associated with in‐stream nutrient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Van Beek et al (2007) found that nutrient-rich peat layers will remain a potential source of nutrients in surface water in many peat polders in the western part of the Netherlands. Mourad and van der Perk (2009) found that the spatial patterns of nitrate and phosphate concentrations in the Ahja River catchment in Estonia were related to spatial differences in urban and agricultural land use proportions. Vermaat et al (2010) studied 13 peat polders in the Netherlands and reported that agricultural land use largely determined the variability in nutrient concentrations and loads.…”
mentioning
confidence: 96%